Proceedings of the 28th International Conference on Scientific and Statistical Database Management 2016
DOI: 10.1145/2949689.2949698
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dependencies Unleashed for Scalable Data Exchange

Abstract: International audienceWe address the problem of efficiently evaluating target functional dependencies (fds) in the Data Exchange (DE) process. Target fds naturally occur in many DE scenarios, including the ones in Life Sciences in which multiple source relations need to be structured under a constrained target schema. However, despite their wide use, target fds' evaluation is still a bottleneck in the state-of-the-art DE engines. Systems relying on an all-SQL approach typically do not support target fds unless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…SELECT DISTINCT R.a, append(' _ Sk _ f(',R.a,')') FROM R (10) The parallel chase [11] weakens line 6 to check whether h is active in I, rather than in µ(I ∪ N); since I is fixed in an iteration, this can make checking active triggers much easier to implement. Known acyclicity conditions [18] ensure termination of the parallel chase, and the solution is deterministic, although it may be larger than the one produced by the restricted chase.…”
Section: Insert Into R(ab)mentioning
confidence: 99%
See 2 more Smart Citations
“…SELECT DISTINCT R.a, append(' _ Sk _ f(',R.a,')') FROM R (10) The parallel chase [11] weakens line 6 to check whether h is active in I, rather than in µ(I ∪ N); since I is fixed in an iteration, this can make checking active triggers much easier to implement. Known acyclicity conditions [18] ensure termination of the parallel chase, and the solution is deterministic, although it may be larger than the one produced by the restricted chase.…”
Section: Insert Into R(ab)mentioning
confidence: 99%
“…CHASEFUN [10] is a more recent data exchange system. It supports only s-t TGDs and functional dependencies, and it implements a variant of the unrestricted Skolem chase in which TGD and EGD chase steps are ordered to reduce the size of the intermediate chase results.…”
Section: The Systems Testedmentioning
confidence: 99%
See 1 more Smart Citation
“…Related also the chase [29], a classical tool in the relational dependency theory. The chase has been employed in data exchange [30], [31], data repairing [32] and query rewriting [33], with relational tuple-generating dependencies (TGDs) and equality generating dependencies (EGD; see [34] for a survey). As remarked earlier, the chase has also been studied for FDs on RDF [4], [5] and for GEDs [2].…”
Section: Related Workmentioning
confidence: 99%
“…We want to review OBDA tools that can deal with Datalog ± programs, and their chase procedure is integrated with an RDBMS. The interesting research that we found is [Benedikt et al, 2017] which provides a benchmark, ChaseBench, by running a variety range of experiments over different tools, ChaseFun [Bonifati et al, 2016], DEMo [Pichler and Savenkov, 2009], Llunatic [Geerts et al, 2013], and PDQ [Benedikt et al, 2015]. The primary reason that some of these tools are proposed is solving the problem of data exchange (DE).…”
Section: State Of the Artmentioning
confidence: 99%